Gavage‐administered lactoferrin promotes palatal expansion stability in a dose‐dependent manner. (13th August 2021) - Xiao, Xiaoyue; Cheng, Ye; Huang, Li; Liu, Ruojing; Zou, Shujuan; Chen, Jianwei
Abstract: Objective: To investigate the effects of different lactoferrin concentrations on mid‐palatal suture bone remodeling during palatal expansion and relapse in rats. Materials and Methods: Thirty‐two 5‐week‐old male Wistar rats were randomly divided into four groups: EO (expansion only), E+LF1 (expansion plus 10 mg/kg/day daily LF), E+LF2 (expansion plus 100 mg/kg/day daily LF), and E+LF3 (expansion plus 1 g/kg/day daily LF). Thereafter, micro‐computed tomography and micro‐morphology of the mid‐palatal suture were analyzed on day 7 and day 14, respectively. Results: The arch widths were increased in all the four groups after expansion, and there was no significant difference among them on day 7. After relapse, however, the arch width in the E+LF3 group was significantly larger compared with EO group. In E+LF3 group and E+LF2 group, new bone formation and osteoblast number were enhanced with up‐regulated expression of osteocalcin and collagen type I, while the expression of cathepsin K‐positive cells was downregulated in E+LF3 group. Conclusion: Lactoferrin gavage administration might increase the stability of palatal expansion and reduce relapse in a concentration‐dependent manner by enhancing bone formation and inhibiting resorption. LF administration may be promising for optimizing the maxillary expansion outcome.